Peningkatan Hasil Belajar Peserta Didik Kelas VIII SMP Negeri 2 Tarabintang melalui Metode Pembelajaran Problem Based Learning - Melati P. Lumbantoruan (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This study aims to improve the learning outcomes of eighth-grade students at SMP Negeri 2 Tarabintang in the subjects of Catholic Religious Education and Ethics through the implementation of the Problem-Based Learning (PBL) model. This method was chosen as a solution to the low interest and learning outcomes of students, especially in understanding the material of the Church as a Sign and Means of Salvation. This study employs a Classroom Action Research (CAR) approach conducted in two cycles. Each cycle involves the stages of planning, action implementation, observation, and reflection. The results of the study indicate that the implementation of the PBL model successfully improved students' learning outcomes in the cognitive, affective, and psychomotor aspects. In the first cycle, the average value of student test results reached 76, which increased to 85 in the second cycle. In addition, students' active participation in group discussions increased significantly, as seen from the observation results that showed an increase in students' ability to identify problems, provide alternative solutions, and appreciate the perspectives of others. In conclusion, the implementation of the Problem-Based Learning (PBL) model has proven effective in improving students' learning outcomes, both in terms of knowledge and social skills. The application of this model not only increases students' understanding of the material taught but also enhances students' active participation and motivation to learn. It is recommended that teachers continue to apply this method in teaching, especially in subjects that require active student involvement in problem-solving.